Undergraduates in computer science and information technology using the internet as a resource - Mohd Sharif, M.S.; Zainab, A.N. (2004)

(untitled)
The study explores the use of the Internet by final year undergraduates at the Faculty of Computer Science and Information Technology during the initial stages of their Final Year Project. A total of 360 survey returns indicate that undergraduates heavily use the Internet (98%). Other sources, which the students use is also listed. The students seem to exhibit high level of information literacy. They utilize various search strategies while searching the Internet, able to locate and retrieve information, able to analyse and evaluate information gathered. They use various methods to validate the authenticity of the information obtained and able to synthesize what they have read to shape the initial chapters of their final year report. The students are also aware of ethical issues surrounding the use of Internet resources. A focus group of 14 undergraduates who kept a diary of their information seeking and use behaviour, provide a clearer picture of the students behaviour and the approaches adopted when using the Internet. The outcome of the approaches is also explained.